Oral Solid Dosage form Modification in Community Pharmacies of Kavrepalanchok and Bhaktapur Districts of Nepal - Shrestha, J.; Shrestha, A.; Shrestha, B.; Gamal, K.; Manandhar, S.; Koju, S.; Koju Shrestha, R. (Kathmandu University Medical Journal, 2022)
Background People may modify their oral solid dosage form of medicine to deal with problem faced during medicine administration. The modification of dosage form may adversely affect the quality, safety and efficacy of the medicine. Objective To investigate the causes and practices of oral solid dosage form modification among the consumers going to community pharmacies. Method A descriptive, cross-sectional study was conducted in five community pharmacies of Kavrepalanchok and Bhaktapur districts of Nepal. The consumers visiting these pharmacies for their oral solid dosage form of medicine were invited to participate in interview using structured questionnaire. Result Among 419 participants,13.6% of participants reported having problem of taking intact medicine. Most of them (12.4% of total participants) experienced difficulty swallowing the medicine. The swallowing difficulty is significantly associated with age and sex (p < 0.05). Around one third (36.8%) of participant with medicine administration problem modified the dosage form of medicines. One quarter of medicine dosage form modifications (25.0%) were inappropriate. Medicine dosage form modification is associated with age and number of daily medicine intake (p < 0.05). Among participants modifying dosage form of medicines, 66.7% were advised to do so mainly by family and friends; 33.3% were modifying on their own and 76.2% were unaware of possible effects of medicine dosage form modification. About 62.3% of total participants were never asked about any problems on taking medicines by doctor/pharmacists. Conclusion Difficulty swallowing medicines and medicine dosage form modification were prevalent in the Nepalese population. Medicine dosage form modifications also involved inappropriate modifications due to specialized design of such dosage forms. So, it seems important to provide proper counseling while dispensing such dosage forms.